MАГИСКИ ФОРМУЛИ И МОЛИТВИ ЗА ЗДРАВЈЕ ВО МАКЕДОНСКИТЕ ЛЕКАРСТВЕНИЦИ ОД XIX ВЕК (Filološke studije, 2019)
Medicine books are manuscripts that contain recipes for making different medicines, and procedures for treating different diseases, mainly in people but also in animals, as well as different practical advices on some usual activities: making brandy, painting a fence, etc. Materials from four Macedonian medicine books, written in different places in Macedonia throughout 19th century, are used in this abstract. Although it is unquestionable that the medicine books largely rely on the empirical branch, one can find examples of the so called animistic-magical branch of the folk medicine, that is to say one can find interesting examples of using the curative magic, i.e. incantations, for healing certain diseases in people and in animals, for dispersing evil spirits, etc. Those procedures were usually accompanied by appropriate magical formulas and prayers being uttered. They differ in content, structure, purpose, and in meaning. Thus, it can indirectly instruct that a certain prayer be said, for example the prayer Our Father, prayers dedicated to Virgin Mary and other saints, etc., or it can contain the whole text of the prayer that, usually, needs to be said three times. Sometimes there are also prayers followed by incantations that rhyme, which are used to drive off the demonic force into the darkness or lie to the demon causing the disease tricking it into going to a better place. These incantations are also well known throughout the south-Slavic region. As with the prayers, magic formulas are not necessarily given explicitly, but they instruct on how to pronounce them. But the prayers in Greek, Latin, and sometimes in other languages that are not pronounced at all but rather written on a particular spot are especially interesting. These are texts for amulets. Even though they are not quite clear, and sometimes they might not have a meaning at all, these formulas clearly point to man's primeval faith in the magical power of the word, especially if it is in a language that one barely knows or in an unknown language. The medicine books contain formulas for treating similar health problems in animals (in which case the text is written on the hoof of the horse) and in people (in which case it is written on the nail). Sometimes these formulas are written on bread or paper.